La estimulación temprana y su influencia en el aprendizaje de las niñas y niños del primer grado de educación general básica paralelo A y B del jardín de infantes “Pío Jaramillo Alvarado” de la ciudad de Loja periodo 2013-2014 - Balcázar Chamba, Nimia Vanessa (2014)
he present investigation is of descriptive character, called: The early stimulation and its influence on the learning of the girls and children of the first grade of Basic General Education parallel A and B of kindergarten “Pío Jaramillo Alvarado” of the city of Loja period 2013-2014. The general objective was: to know that way influences the early stimulation in the learning of the girls and children of the first grade of Basic General Education parallel A and B kindergarten “Pío Jaramillo Alvarado” of the city of Loja period 2013-2014. Use the following methods: Scientific, Inductive-Deductive, Descriptive, analytical, Systematic and Statistical. The techniques used were: the survey directed to the to establish the activities of early stimulation and learning that exists in the home, and also on observation guide, applied to the girls and children to assess the learning. The results of the teachers surveyed answer, that if the early stimulation in the childrens: since that we most apply the cognitive area, motive, the language and the area partner-emotional. Manifesting so that stimulation early affects learning of the girls and children of the first grade of Basic General Education. The results of the parents surveyed manifest that of learning is very important in the daily living of the child, since it stimulates kids through game and who ask for advice to teachers. After the tabulation of results of the observation guide applied to girls and children is concluded in a positive way, that children who receive stimulation by their teacher during the daily wok, using so the technical of the game.